2015
DOI: 10.1115/1.4029726
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Experimental and RANS-Based Numerical Studies of the Decay of Grid-Generated Turbulence

Abstract: This paper presents both experimental and numerical studies of the statistical properties of turbulent flows at moderate Reynolds number (Reλ = 100) in the context of grid-generated turbulence. In spite of the popularity of passive grids as turbulence generators, their design relies essentially on empirical laws. Here, we propose to test the ability of simple numerical simulations to capture the large scale properties (root-mean-square (rms) velocity, turbulence decay, pressure drop, etc.) of the turbulence do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…The present work attempts to simulate freely decaying isotropic homogenous turbulence using Large Eddy Simulation (LES). The current results show good quantitative agreement with the previous experimental results from [10], [15], [16]. Three different correlations were formulated which can be useful in estimating the local and initial values of turbulent parameters (i.e.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The present work attempts to simulate freely decaying isotropic homogenous turbulence using Large Eddy Simulation (LES). The current results show good quantitative agreement with the previous experimental results from [10], [15], [16]. Three different correlations were formulated which can be useful in estimating the local and initial values of turbulent parameters (i.e.…”
Section: Discussionsupporting
confidence: 87%
“…Numerous wind tunnel experiments have focused on generating homogeneous turbulence by different grids; passive [8], [9], active [10], [11], and multiscale (fractal) [12][13][14][15]. Numerical steady-state simulations [16] have also been carried out to reconcile the differences but no quantitative data have been presented at the inlet that would characterize the decay of turbulence downstream of a grid based on those specified initial conditions. A variation in the observed decay exponent n (from 1.0 to 1.4) implies that there might not be a universal state of decay mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…However, the accuracy of the hot-wire sensor used in the test is insufficiently high. Torrano [21] presented experimental and numerical studies of the statistical properties of turbulent flows at moderate Reynolds number in the context of grid-generated turbulence, but the simulation error was not analyzed. Suzuki [22] proposed a validation scheme for the effect of wind tunnel blockage on a decaying gridgenerated turbulence.…”
Section: State Of the Artmentioning
confidence: 99%
“…It is found that the turbulence intensity generated by the single grid structure is larger than the other two cases in the production region, which is due to the stronger vortex shedding effect, and the fractal grid suppresses the vortex shedding. Torrano [5] compared experimental measurement with RANS-Based numerical studies of the decay of grid-generated turbulence. The result showed the ability of RANS-based numerical simulations to capture the large scale properties generated by grid is within an acceptable accuracy.…”
Section: Introductionmentioning
confidence: 99%